Cellulose nanocrystals from passion fruit peels waste as antibiotic drug carrier. (1st November 2017) - Wijaya, Christian J.; Saputra, Stephanie N.; Soetaredjo, Felycia E.; Putro, Jindrayani N.; Lin, Chun X.; Kurniawan, Alfin; Ju, Yi-Hsu; Ismadji, Suryadi
Highlights: Cellulose nanocrystals (CNC) was extracted from passionfruit peels waste. CNC was employed as drug excipient for tetracycline (TC) delivery. High adsorption capacity of CNC toward TC was achieved through pH adjustment. Abstract: Due to its excellent chemical and physical properties, cellulose nanocrystals (CNC) possess many potential advanced functional applications. In this study, CNC was extracted from natural product by hydrolyzing cellulose segment of passionfruit peels using sulphuric acid solution. The capability of CNC as drug carrier was tested toward tetracycline antibiotic. The drug loading processes were carried out at various pH (3–7) with the optimum uptake of tetracycline achieved at pH 3. The in vitro release of tetracycline drug was carried out in phosphoric buffer medium with two different pH conditions at 37 °C. The highest release of tetracycline (82.21%) was achieved at pH 7.2, while the lowest one (25.1%) was achieved at pH 2.1, where the release pattern follow a second order kinetic model. This study highlight the potential application of CNC derived from natural resources as drug carrier without harmful chemical excipients that comply with health safety, biocompatible, biodegradable.